Facile synthesis of graphene oxide with significant enhanced properties for optoelectronic and energy devices. Issue 6 (15th April 2018) - Aslam, Samia; Mustafa, Faiza; Ahmad, Muhammad Ashfaq
Abstract: Graphite is a promising source for graphene and its derivatives (GO and RGO) but several lengthy processess are involved in the production and tuning of its properties. In this work, graphene oxide nanosheets (GNSs) were synthesized by a one step, environment friendly and cost effective electrolysis technique. The GNSs were characterized by XRD, AFM, UV-vis-NIR, Raman, FTIR, photoluminescencespectroscopies and thermogravimetric analysis (TGA). The XRD pattern confirmed the formation of GNSs. The UV-Vis analysis confirmed quantum confirnment effect in GNSs with increased band gap of 5.4 eV. PL spectrum showed emission peaks in visible to Infrared region. The sheets possessed excellent thermal stability confirmed from TGA analysis. The FTIR results verified the existence of oxygen-containing functional groups (OFGs) in the GNSs. The I D / I G ≈ 0.85 obtained from Raman Spectra showed high quality GNSs with less defects. The AFM and SEM results showed wrinkles with high grain surface area and roughness.The obtained results showed significantly enhanced properties and indicated that synthesized GNSs are cerdible potential candidates for optoelectronic devices including solar cells, supercapacitors, electrochemical and bio sensors, biomarkers and also suitable for low temperature fuel cells.